Effectiveness of a nasal spray containing essential oil from Citrus microcarpa Bunge on the SEM profile of Aspergillus fumigatus mycelium - Ananda, Revian; Mayasari, Ulfayani; Nasution, Rizki amelia (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2026)
Deteriorating air quality during seasonal transitions contributes to the increased growth of pathogenic microorganisms, including Aspergillus fumigatus, which may lead to adverse health impacts. Synthetic antifungal agents may induce resistance and undesirable side effects, thereby promoting interest in safer natural alternatives. This study aimed to evaluate the antifungal effectiveness of a nasal spray formulated with kasturi orange (Citrus microcarpa) peel essential oil against A. fumigatus. The essential oil was extracted through steam distillation and tested at five concentrations to identify the most effective range, after which three concentrations exhibiting the strongest antifungal activity were formulated into a nasal spray. Antifungal effectiveness was assessed using the disc diffusion method, morphological alterations of fungal hyphae were observed using Scanning Electron Microscopy (SEM), and statistical analysis was performed using Analysis of Variance (ANOVA). The results showed that the nasal spray demonstrated significant antifungal activity (p < 0.05), with inhibition zone diameters of 12.8 mm, 16.1 mm, and 20.5 mm at essential oil concentrations of 10%, 20%, and 30%, respectively. Although the highest concentration produced the largest inhibition zone, excessively high essential oil levels do not necessarily improve antifungal performance and may trigger adaptive responses approaching resistance. SEM observations confirmed notable cellular damage, including hyphal lysis, cell wall thinning, and structural shrinkage following exposure to the nasal spray formulation. In conclusion, kasturi orange peel essential oil is effective when formulated as a nasal spray to inhibit A. fumigatus, with 20% identified as the most suitable concentration for further product development.